2014
DOI: 10.1111/imb.12107
|View full text |Cite
|
Sign up to set email alerts
|

Methuselah‐likegenes affect development, stress resistance, lifespan and reproduction inTribolium castaneum

Abstract: Methuselah (Mth) is associated with lifespan, stress resistance and reproduction in Drosophila melanogaster, but Mth is not present in nondrosophiline insects. A number of methuselah-likes (mthls) have been identified in nondrosophiline insects, but it is unknown whether the functions of mth are shared by mthls or are divergent from them. Five mthls have been identified in Tribolium castaneum. Although they have different developmental expression patterns, they all enhance resistance to starvation. Only mthl1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Previous studies have demonstrated that D. melanogaster Mth-likes (homologous receptors of Mth) show high similarity to Mth and contain similar seven transmembrane (7tm) domains [3,37]. In our study, these three putative Mth-likes consisted of seven conserved transmembrane domains, which is consistent with the finding of a recent study in T. castaneum [38], although they only shared a moderate degree of sequence identity (24%, 29%, and 25% for Mth-like1, Mth-like2, and Mth-like5, respectively) with the Mth (NP-523871.1) of D. melanogaster .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous studies have demonstrated that D. melanogaster Mth-likes (homologous receptors of Mth) show high similarity to Mth and contain similar seven transmembrane (7tm) domains [3,37]. In our study, these three putative Mth-likes consisted of seven conserved transmembrane domains, which is consistent with the finding of a recent study in T. castaneum [38], although they only shared a moderate degree of sequence identity (24%, 29%, and 25% for Mth-like1, Mth-like2, and Mth-like5, respectively) with the Mth (NP-523871.1) of D. melanogaster .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in D. melanogaster have shown that mth was expressed in both embryos and third-instar central nervous system (CNS) or discs, mth-like1 and mth-like5 were expressed in the embryo, while mth-like2 was not detected in whole embryos or third-instar brain and imaginal discs using in situ hybridization techniques [3]. A recent study suggested that the mRNA levels of mth-like1 of T. castaneum were highly expressed at the late egg, pupa, and early adult stage, and mth-like2 and mth-like5 were highly expressed at the early embryonic and late pupal stages [38]. Similarly to T. castaneum mth-like genes, mth-like genes of D. helophoroides were expressed throughout all of the larval, pupal, and adult stages, but to some extent they display different expression patterns, indicating that mth-like genes ( mth-like2 and mth-like5 ) of D. helophoroides were likely to have similar functions involved in larval and pupal development and the process of eclosion to T. castaneum mth-like genes, while functional divergence most likely occurred between T. castaneum and D. helophoroides mth-like genes ( mth-like1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations